Implementasi OWASP untuk Analisis Kerentanan dan Keamanan pada Sistem Informasi Akademik Terintegrasi Universitas Bina Darma - Tamsir Ariyadi; Hidayatul Fadli; Taufik Akbar; Muhammad Bimo Prihandoko (Yayasan Literasi Sains Indonesia, 2025)
The advancement of information technology has brought significant changes to the way teaching and learning processes are carried out in higher education, one of which is through the implementation of the Siska (Integrated Academic Information System). While this system provides many benefits, it also introduces potential security risks that could threaten data integrity and disrupt the learning process. This study aims to analyze the vulnerabilities on the website https://siska.binadarma.ac.id/ of Universitas Bina Darma using the OWASP (Open Web Application Security Project) framework. This method assists in identifying potential security loopholes that could be exploited by unauthorized parties. The research examines these vulnerabilities based on the ten key categories proposed in the OWASP Top 10. The results of this analysis are expected to offer valuable recommendations to enhance the security of the Siska system at Universitas Bina Darma, ultimately protecting user data and ensuring that the learning process continues safely and smoothly.